Ahlfors Theorems for Differential Forms - O. Martio; V. M. Miklyukov; M. Vuorinen (Abstract and Applied Analysis)
Some counterparts of theorems of Phragmén-Lindelöf and of Ahlfors are proved for differential forms of 𝒲𝒯-classes.